Sex classification using the three-dimensional tibia form or shape including population specificity approach - Brzobohatá, Hana; Krajíček, Václav; Horák, Zdeněk; Velemínská, Jana (Journal of forensic sciences, 2015)
The aims of this study were to enable geometric morphometric sex classification using tibial proximal and distal sexual dimorphism and to evaluate the secular trend of tibial shape/form from the early 20th century to the present day. The study samples consisted of 61 adult tibias from an early 20th-century Czech population and 57 three-dimensional tibias from a 21st-century population. Discriminant function analysis with cross-validation was carried out to assess the accuracy of sex classification. Shape analysis revealed significant sex differences in both tibial extremities of the 21st-century sample and in the proximal tibia of the 20th-century population. Sex-based divergence varied between the analyzed samples, raising the issues of population specificity and diachronic change. Classification using tibial form was more successful than using tibial shape. The highest values of correct assignment (91.80% and 88.52%) were found using the form from the early 20th Czech population.
Keywords: dospělí; Forensic Anthropology; Tomography, X-Ray Computed; History, 21st Century; Humans; lidé středního věku; sexual dimorphism; Middle Aged; Young Adult; mladý dospělý; dějiny 20. století; zobrazování trojrozměrné; Discriminant Analysis; History, 20th Century; mužské pohlaví; dějiny 21. století; určení pohlaví podle kostry; Adult; optical scanning; tibie; ženské pohlaví; analýza hlavních komponent; Principal Component Analysis; Sex Determination by Skeleton; Imaging, Three-Dimensional; soudní antropologie; geometric morphometrics; lidé; forensic science; tibia; computed tomography-derived models; počítačová rentgenová tomografie; Aged; senioři; Male; diskriminační analýza; Tibia; Female